Identifying Factors Influencing Career Disengagement in Highly Educated Women - Okonkwo, Adaeze; Dlamini, Thandiwe (Psychology of Woman Journal, 2024)
Objective: This study aimed to explore the underlying factors that contribute to career disengagement among highly educated women in South Africa.Methods and Materials: A qualitative research design was employed to investigate the lived experiences of 24 highly educated women who had voluntarily disengaged from their professional careers. Participants were recruited through purposive sampling and met the criteria of holding at least a postgraduate qualification and having exited or reduced participation in formal employment. Data were collected through in-depth semi-structured interviews, each lasting between 45 and 70 minutes. Interviews were transcribed verbatim and analyzed using NVivo software. Thematic analysis was conducted through an inductive coding process, encompassing open, axial, and selective coding stages. The study followed the principle of theoretical saturation, and credibility was ensured through member checking and peer debriefing.Findings: Thematic analysis revealed four main themes influencing career disengagement: structural and institutional barriers, sociocultural expectations and pressures, psychological and emotional burnout, and life re-prioritization and autonomy. Subthemes included inflexible work arrangements, gendered organizational cultures, internalized role conflict, emotional exhaustion, and the pursuit of meaningful, autonomous lifestyles. Participants frequently described systemic inequities, social judgment, and identity-related struggles as contributing factors. For many, disengagement was not solely a response to adverse conditions but a deliberate decision to prioritize well-being, autonomy, and personal fulfillment.Conclusion: Career disengagement among highly educated women is shaped by a complex interplay of systemic, cultural, and psychological factors. These findings highlight the need for organizational and societal reforms to foster inclusive, flexible, and meaningful career pathways for women.